Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 4 - Polynomials - 4.6 Special Products - 4.6 Exercise Set - Page 278: 116



Work Step by Step

RECALL: $(a+b)(c+d)=ac+ad+bc+bd$ (more popularly known as the FOIL method) Use the FOIL method to obtain: $(2x+5)(x-4)=(x+5)(2x-4) \\2x(x) + 2x(-4)+5(x) + 5(-4)=x(2x)+x(-4)+5(2x)+(5)(-4) \\2x^2-8x+5x-20=2x^2-4x+10x-20 \\2x^2-3x-20=2x^2+6x-20$ Put all the terms with a variable on the left side and the constants on the right side. Note that when you move a term from one side of the equation to the other, it changes to its opposite. $2x^2-3x-2x^2-6x=-20+20 \\(2x^2-2x^2)+(-3x-6x)=0 \\0+(-9x)=0 \\-9x=0 \\\frac{-9x}{-9}=\frac{0}{-9} \\x=0$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.